Significantly Enhanced Electrostatic Energy Storage Performance of Flexible Polymer Composites by Introducing Highly Insulating‐Ferroelectric Microhybrids as Fillers. Issue 5 (7th December 2018) - Luo, Suibin; Yu, Junyi; Yu, Shuhui; Sun, Rong; Cao, Liqiang; Liao, Wei‐Hsin; Wong, Ching‐Ping
Abstract: A hybrid nanoparticle, consisting of BaTiO3 nanoparticles tightly embedded in bronnitride (BN) nanosheets, has been fabricated based on a daring supposition that BN may act as a host to incorporate ferroelectric nanoparticles to improve insulation and polarization under a high electric field. Using the hybrids as fillers in poly(vinylidene fluoride) (PVDF) composites, a high electric breakdown strength ( Eb ≈580 kV/mm), which is 1.76 times of the PVDF film, is obtained when the filler content is 5 wt%. A large displacement (9.3 µC/cm 2 under 580 kV/mm) is observed so as to obtain a high discharged energy density ( Ud ≈17.6 J/cm 3 ) of the BT@BN/PVDF composites, which is 2.8 times of the PVDF film. The enhancement ratio of Eb achieved in this study demonstrates the highest among the reported results. This hybrid structure of fillers provides an effective way to adjust and improve the energy storage properties of the polymer‐based dielectrics. Abstract : BaTiO3 @BN hybrids with the structure of barium titanate nanoparticles embedded in bronnitride nanosheets are fabricated, which act as fillers in poly(vinylidene fluoride)‐based composites. The electric breakdown strength and discharged energy density of the composites are significantly enhanced owing to the reduced surface charge density and the enhanced displacement.